Crangonyx islandicus N & Kristjánsson, 2006, sp. nov. - N, Jörundur Svava R S S O; Kristjánsson, Bjarni K. (Annual Research & Review in Biology, 2006)
Crangonyx islandicus sp. nov. (Figs 1–6) Material examined Holotype. Female, 6.8 mm, non-ovigerous, brood plates with setae, Vatnsvik, 64°14.46´N, 21°03.19´W, Thingvallavatn, Southwest Iceland, 12 July 2001, groundwater inflow to the lake, 4°C, 30 ppm conductivity, electric fishing, coll. B.K. Kristjánsson, IMNH 2164. Paratypes. Vatnsvik, 64°14.46´N, 21°03.19´W, Thingvallavatn, Southwest Iceland, 8 May 2001, 21 specimens (drawn paratype included), groundwater inflow to the lake, electric fishing, coll. B.K. Kristjánsson, IMNH 2165; Vatnsvik, 64°14.46´N, 21°03.19´W, Thingvallavatn, Southwest Iceland, 12 July 2001, 7 specimens, groundwater inflow to the lake, electric fishing, coll. B.K. Kristjánsson, IMNH 2166; Nautavakir, 64°00.876´N, 20°53.018´W, Southwest Iceland, 1 August 2003, 6°C, 60 ppm conductivity, coll. B.K. Kristjánsson & J. Svavarsson, 1 specimen, IMNH 2167. Other material examined Vatnsvik (64°14.46´N, 21°03.19´W), Thingvallavatn, Southwest Iceland, electric fishing, coll. B.K. Kristjánsson: 5 September 2000, 1 specimens; 6 September 2000, 6 specimens; 25 February 2001, 22 specimens; 31 March 2001, 18 specimens; 7 May 2001, 2 specimens; 21 May 2001, 27 specimens; 12 June 2001, 7 specimens; 25 July 2001, 42 specimens; 6 June 2002 (ethanol preserved), 10 specimens; 30 June 2003, 16 specimens. Skútavík, Thingvallavatn, Southwest Iceland, approximately 64°08.5´N, 21°02.5´W, electric fishing, coll. B.K. Kristjánsson, 2 specimens; Nautavakir, Grímsnes, Southwest Iceland, 64°00.876´N, 20°53.018´W, 7 June 2002, from the stomach of arctic charr ( Salvelinus alpinus 60.9 mm) fished in groundwater outflow, electric fishing, coll. B.K. Kristjánsson, 1 specimen, damaged; Spring at Gunnarsholt, South Iceland, 21 July 2004, electric fishing, coll. B.K. Kristjánsson, 1 specimen; Keldur, spring at area 1, South Iceland, 63°49.346´N, 20°04.561´W, 21 July 2004, 2.9°C, 110 ppm conductivity, electric fishing, coll. B.K. Kristjánsson, 1 specimen; Lind (spring close to Keldur), South Iceland, 63°49.607´N, ...